Anatomy of Victory : Why the United States Triumphed in World War II, Fought to a Stalemate in Korea, Lost in Vietnam, and Failed in Iraq - Caldwell, John D. (Rowman & Littlefield Publishers, 2018)
This groundbreaking book provides the first systematic comparison of America's modern wars, analyzing how and why the United States has moved from success to failure since WWII. As the United States enters a new period of uncertainty in the world, Caldwell makes the compelling case that leaders must think, plan, and prepare before shooting.